A new four-component reaction involving the Michael addition and the Gewald reaction, leading to diverse biologically active 2-aminothiophenes. Issue 18 (26th April 2017) - Thomas, Joice; Jana, Sampad; Sonawane, Mahendra; Fiey, Bert; Balzarini, Jan; Liekens, Sandra; Dehaen, Wim
Abstract : A Gewald-four component reaction has been successfully developed for the synthesis of a series of compounds containing an indole and a 2-aminothiophene moiety separated by a methylene spacer having anti-proliferative activity. Abstract : The Gewald three-component reaction yielding highly substituted 2-aminothiophene heterocycles has been known for a long time and holds an extraordinary potential in the pharmaceutical industry. Herein, we describe a four-component reaction initiated by the conjugate addition of different indole derivatives to α, β-unsaturated carbonyl compounds. This is followed by an in situ Gewald three-component reaction which results in the formation of a compound containing an indole and a 2-aminothiophene moiety separated by a methylene spacer. We also examined the impact of the use of other nucleophilic components such as pyrrole derivatives on this MG-4CR (Michael–Gewald four component reaction). All these synthesized compounds were tested for anti-proliferative activity and three of them showed activity in the nanomolar range.